Correlation of Multiple Acromion Morphological Parameters on Radiographs in a Geriatric Chinese Population and Its Clinical Significance. (8th October 2021) - Yu, Mingyang; Zhu, Xiaoming; Zhang, Yao; Guo, Lin; Li, Dongyi; Tian, Fengde; An, Ning; Hao, Ruihu; Wang, Changcheng
Introduction: Previous clinical studies have reported associations between the acromion index, lateral acromion angle, and critical shoulder angle and the occurrence of rotator cuff tears. The objective of this study was to analyze the correlations of these different anatomic parameters in geriatric Chinese Population. Methods: Healthy geriatric Chinese participants (n = 66) and geriatric Chinese patients with rotator cuff tears (n = 70) identified between January 2019 and October 2020 were included in this study. Standardized true anteroposterior radiographs were used to measure the acromion index, lateral acromion angle, and critical shoulder angle in each study participant. Results: The mean acromion index was significantly larger, the mean lateral acromion angle was significantly smaller, and the mean critical shoulder angle was significantly larger in geriatric patients with full-thickness rotator cuff tears compared with geriatric healthy participants. Conclusion: There were a negative linear relationship between the acromion index and lateral acromion angle and a positive linear relationship between the acromion index and critical shoulder angle in geriatric patients with rotator cuff tear and geriatric healthy participants; we termed this phenomenon "Hypothesis of Acromion Index." The acromion index, lateral acromion angle, and critical shoulder angle are independent predictors of rotator cuff tears in a geriatric Chinese population.